2012
DOI: 10.1515/cclm-2011-0757
|View full text |Cite
|
Sign up to set email alerts
|

Human epididymis protein 4 as a serum marker for diagnosis of endometrial carcinoma and prediction of clinical outcome

Abstract: HE4 is more sensitive and specifi c than CA125in distinguishing endometrial cancer patients from women with normal endometrium, regardless of tumour stage and grade. sHE4 appears to be associated with a more aggressive tumour variant and it could be clinically useful, in identifying high-risk endometrial cancer patients, for a tailored surgical and postoperative therapy. HE4 significant correlation with decreased Overall Survival, Disease Free Survival and Progression Free Survival suggests its potential role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
52
2
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 27 publications
10
52
2
6
Order By: Relevance
“…The number of patients with histological grading G1, G2, and G3 was 34 (73.9%), 9 (19.5%), and 3 (6.5%), respectively. Serum HE4 levels in these groups of patients were 91.70 ,120, and 213 pmol/L, respectively, while CA125 levels were 16 A total of 33 (94.29%) patients were diagnosed with other pathologies, including 17 (48.57%) women with endometrial polyps, 2 (5.71%) with hyperplasia without atypia, and 14 (40.00%) with both, endometrial polyp and hyperplasia without atypia. The statistical significance of the S-W test was < 0.001 for both tumor markers.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The number of patients with histological grading G1, G2, and G3 was 34 (73.9%), 9 (19.5%), and 3 (6.5%), respectively. Serum HE4 levels in these groups of patients were 91.70 ,120, and 213 pmol/L, respectively, while CA125 levels were 16 A total of 33 (94.29%) patients were diagnosed with other pathologies, including 17 (48.57%) women with endometrial polyps, 2 (5.71%) with hyperplasia without atypia, and 14 (40.00%) with both, endometrial polyp and hyperplasia without atypia. The statistical significance of the S-W test was < 0.001 for both tumor markers.…”
Section: Resultsmentioning
confidence: 87%
“…HE4, along with CA125 and the menopausal status, is used to determine the risk of malignancy through an algorithm in patients with adnexal tumors [15]. Recent studies have shown that HE4 levels are elevated in patients with EC [11,16,17]. The role of tumor markers in detecting early stages of EC may be limited since postmenopausal bleeding is an early symptom of the disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies without a clear documentation of cutoff values reported the same specificity of 90%, while the sensitivities are 95% and 98%, respectively [21,22]. Other three studies using 50-70 pM cutoff values reported 78.8% sensitivity and 100% specificity [23][24][25].…”
Section: Introductionmentioning
confidence: 92%
“…HE4 has been reported to be upregulated in several types of cancers including those of the ovary (16), endometrium (17), lung (18,19), breast (7,15), stomach and pancreas (20). The expression of HE4 in ovarian cancer was initially reported in 1999 (16), and it was subsequently cleared as a new biological marker of ovarian cancer in 2003 (21).…”
Section: Introductionmentioning
confidence: 99%